Questioning gender : the representation of race and gender in global and local print media responses of the Caster Semenya saga. - Bhula, Vidhya (My University, 2011)
Examining the print media representations of South African runner, Caster Semenya, is the focal point of this study. Both local and international print media are considered. The dissertation sets out to draw parallels between the representation of Semenya and early 19th century representations of Sarah Baartman. Links between the race of these two women and their “othering” on the basis of their gender are drawn. The study explores the medical and scientific justifications for “othering” these two women, the lack of agency that is attributed to both Semenya and Baartmann, and also discusses the use of humour as a tool of negotiating their “otherness”.
Keywords: Caster Semenya; Gender; Humour; Race; Representation; Sarah Baartmann; Sexulaity; Sport; Women